2016
DOI: 10.1002/2015gl066473
|View full text |Cite
|
Sign up to set email alerts
|

Faulting structure above the Main Himalayan Thrust as shown by relocated aftershocks of the 2015 Mw7.8 Gorkha, Nepal, earthquake

Abstract: The 25 April 2015, Mw7.8 Gorkha, Nepal, earthquake ruptured a shallow section of the Indian‐Eurasian plate boundary by reverse faulting with NNE‐SSW compression, consistent with the direction of current Indian‐Eurasian continental collision. The Gorkha main shock and aftershocks were recorded by permanent global and regional arrays and by a temporary local broadband array near the China‐Nepal border deployed prior to the Gorkha main shock. We relocate 272 earthquakes with Mw>3.5 by applying a multiscale double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 39 publications
(55 reference statements)
3
55
0
Order By: Relevance
“…For the Gorkha earthquake, however, aftershocks do not suggest a clear geometric shape of the fault. Instead, most events are above the MHT [ Bai et al , ], making them difficult to use for rebuilding the fault geometry. Fortunately, high‐quality geodetic data are available, offering us the opportunity to investigate the fault geometry of the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…For the Gorkha earthquake, however, aftershocks do not suggest a clear geometric shape of the fault. Instead, most events are above the MHT [ Bai et al , ], making them difficult to use for rebuilding the fault geometry. Fortunately, high‐quality geodetic data are available, offering us the opportunity to investigate the fault geometry of the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…The bootstrap results indicate centroid depths shallower than 15 km (except for the 25 April aftershock associated with large uncertainty). These estimates are globally consistent with aftershock locations from Adhikari et al [] shown in Figure d and relocations from Bai et al [] showing that more than 65% of aftershocks occurred at depth between 10 and 15 km. Such bootstrap analysis does not fully capture the uncertainty due to inaccuracies in the Earth model used to compute the Green's functions.…”
Section: Depth and Geometry Of The Main Himalayan Thrustmentioning
confidence: 99%
“…The MHT is mainly inferred from source model studies of large and great earthquakes [e.g., Seeber and Armbruster , ; Ni and Barazangi , ; Avouac et al , ; Bai et al , ; Duputel et al , ;] and using balanced geological cross sections [e.g., Schelling and Arita , ; Powers et al , ; Srivastava and Mitra , ]. Some geophysical studies including active [e.g., Prasad et al , ; Gao et al , ] as well as passive source seismic experiments [ Nábělek et al , ; Schulte‐Pelkum et al , ; Acton et al , ; Caldwell et al , ] and magnetotelluric (MT) studies [ Lemonnier et al , ; Unsworth et al , ; Rawat et al , ] were conducted to investigate the geometry of the MHT in different parts of the Himalaya.…”
Section: Introductionmentioning
confidence: 99%